Teaching Reform Measures For Software Engineering Specialization In The Context Of New Engineering - Yang, Songbo (International Journal of Computer Science and Information Technology, 2023)
With the rapid development of science and technology and the deepening of industrial change, the new engineering discipline has become an important direction of higher education reform. As an important part of the new engineering, the reform of software engineering education mode is of great significance for the cultivation of software engineers who can adapt to the future development. This paper firstly introduces the characteristics of software engineering under the background of new engineering discipline, then deeply analyzes the problems existing in the current teaching of software engineering, and puts forward the targeted reform measures. By practicing these reform measures, we can effectively improve the teaching quality of software engineering and cultivate more excellent software engineers with innovative ability and practical ability.